Price setting and inflation persistence: did EMU matter? - Ignazio Angeloni; Luc Aucremanne; Matteo Ciccarelli (European Central Bank (ECB), 2006)
Surprisingly it did not, or at least not directly. Using micro data on consumer prices and sectoral inflation rates from 6 euro area countries, spanning several years before and after the introduction of the euro, we look at whether EMU has altered the behaviour of retail price setting and/or inflation dynamics. We find no evidence that anything has changed around 1999 – if anything, persistence may have slightly increased. At the end of 2001 and in the beginning of 2002 (period surrounding the euro cash changeover) retail price adjustment frequencies, both up and down, increased substantially, while the magnitude of the price adjustment, also both up and down, was smaller than otherwise. However, both settled quickly back to the earlier patterns. On the contrary, we do find evidence of a decline in the persistence of the inflation process in the mid-1990s. This could be due to a structural change in private inflationary expectations due, at least in part, to policies linked to the preparation of EMU; however, this interpretation is weakened by the fact that a similar decline occurred also in the US.
Keywords: E31; E42; E52; 330; Aggregate and Sectoral Inflation; EMU; Inflation persistence; price setting; Eurozone; Inflation; Preisrigidität; Geldpolitik; Theorie; EU-Staaten